2020
DOI: 10.3390/ma13092088
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-Mechanical Simulation of Hybrid Welding of DP/AISI 316 and TWIP/AISI 316 Dissimilar Weld

Abstract: In this paper, hybrid laser-MAG (metal active gas) welding of twinning-induced plasticity (TWIP) and dual-phase (DP) steels with austenitic stainless steel (AISI316) was simulated by means of the finite element method. A thermo-mechanical model, which uses a 3D heat sources, was developed using the software Simufact Welding. The calculated dimensions, shape and distortion of the weld were compared with the experimental results, thence the model was validated. The metallurgical transformations for the DP steel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Laser welding has the characteristics of high energy density, high efficiency, large temperature gradients, high repeatability of the process, and formation of a narrow heat affected zone (HAZ), which can significantly improve welding accuracy and production efficiency in actual processing [7][8][9]. In recent years, the research on laser welding of TWIP steel has mainly focused on the structure and mechanical properties of welded joints under welding process [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Laser welding has the characteristics of high energy density, high efficiency, large temperature gradients, high repeatability of the process, and formation of a narrow heat affected zone (HAZ), which can significantly improve welding accuracy and production efficiency in actual processing [7][8][9]. In recent years, the research on laser welding of TWIP steel has mainly focused on the structure and mechanical properties of welded joints under welding process [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the study confirmed the effectiveness of numerical simulation for predicting the expansion of crack emergence in welded joints. The feasibility of using numerical simulation to optimize the welding parameters and the reliability of the mechanical property analysis of welded joints based on numerical simulation results has been verified in the literature [ 21 , 22 , 23 , 24 , 25 ]. Therefore, based on previous studies, experimental and numerical simulation methods were used in this study for predicting mechanical properties across dissimilar material welded joints.…”
Section: Introductionmentioning
confidence: 96%
“…Although CCT diagrams were thoroughly used, they evaluated the CCT diagrams by performing dilatometry experiments and microstructure and microhardness analysis, which can be time consuming. Previous studies have used CCT diagrams obtained via simulations instead of experiments to overcome this limitation [ 20 , 21 , 22 , 23 ]. In these studies, a single predict CCT diagram was used to predict the phase fraction in the entire welded joint without considering the differences in PAGS with location.…”
Section: Introductionmentioning
confidence: 99%